Metal-tuned W18O49 for efficient electrocatalytic N2 reduction - Yang, M; Huo, R; Shen, H; Xia, Q; Qiu, J; Robertson, AW; Li, X; Sun, Z (American Chemical Society, 2020)
Electrochemical N2 reduction (ENR) offers a promising route for NH3 production. To promote this kinetically sluggish process, the design and development of electrocatalysts with high performance, good durability, low cost, and earth abundance are highly demanded. Here, we report a facile approach for the synthesis of metal-doped ultrafine W18O49 nanowires with significantly enhanced capability for electrocatalytic N2 reduction to produce NH3 within a wide pH range. In particular, the Mo-doped W18O49 catalyst can reduce N2 to NH3 with a faradaic efficiency approaching 12.1% at −0.2 V (versus the reversible hydrogen electrode, vs. RHE) and an NH3 yield rate of 5.3 μgNH3 h–1 mgcat.–1 at −0.5 V (vs. RHE) in 0.1 M Na2SO4, which is about two times higher than that of pristine W18O49. We find occurrence of strong electron transfer from Mo to W, which facilitates N2 adsorption and activation, thus accelerating the ENR to generate NH3. This work provides a simple and effective method to modify metal oxides for efficient electrochemical N2 fixation.